2012
DOI: 10.1038/nutd.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Acylation stimulating protein reduction precedes insulin sensitization after BPD-DS bariatric surgery in severely obese women

Abstract: Objective:The mechanisms involved in early resolution of insulin resistance and type 2 diabetes mellitus after biliopancreatic diversion with duodenal switch (BPD-DS) surgery are still unknown. We evaluated early effects of BPD-DS on plasma acylation stimulating protein (ASP), an adipokine involved in lipid and glucose metabolism.Subjects:32 non-diabetic and 22 diabetic severely obese women (BMI⩾40 kg m−2) were evaluated for body composition and plasma parameters before, 24 h, 5 days, 6 and 12 months after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
11
1
1
Order By: Relevance
“…While restrictions were placed on the specific foods the BPD-DS subjects could consume there was no constraint on the number of calories. Elevated plasma glucose and insulin concentrations 24 h post-surgery in the BPD-DS subjects [Supporting Information Figure 1 and as previously published (30)] supports BPD-DS subjects were not in a fasted state at the time plasma chemerin declined. Accordingly, fasting is likely not responsible for the initial decrease in plasma total chemerin.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While restrictions were placed on the specific foods the BPD-DS subjects could consume there was no constraint on the number of calories. Elevated plasma glucose and insulin concentrations 24 h post-surgery in the BPD-DS subjects [Supporting Information Figure 1 and as previously published (30)] supports BPD-DS subjects were not in a fasted state at the time plasma chemerin declined. Accordingly, fasting is likely not responsible for the initial decrease in plasma total chemerin.…”
Section: Discussionsupporting
confidence: 78%
“…Blood samples were chelated with K 2 EDTA and plasma was separated and stored at 270 C until analysis. Additional subject characteristics and sample analysis procedures are described in the following publications (30)(31)(32)(33).…”
Section: Study Subjects and Samplingmentioning
confidence: 99%
“…10 This study suggested that restoration of ASP sensitivity precedes physiological restitution of INS sensitivity. Interestingly, both C3KO mice receiving chronic recombinant ASP and C5L2KO mice fed a high fat or diabetogenic diet, both examples of induced ASP resistance, are accompanied by onset of INS resistance and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we noted that high presurgical hsCRP levels predicted an unfavourable postbariatric eff ect on insulin resistance. This is counterintuitive and needs further confi rmation, given that in the short run after bariatric surgery, hsCRP reduction predicts improved insulin sensitivity [ 34 ] . Furthermore, it would be interesting to include other adipocytokines into the equation of infl ammation, insulin resistance and eff ectivity of bariatric surgery, such as NAMPT [ 35 ] .…”
mentioning
confidence: 99%